Severe cervical compressive polydiscopathic myelopathy with features of motor neuron disease: A case report - Văcăraș, Vitalie (Clin Case Rep, 2021)
Cervical myelopathy is part of ALS mimic syndrome and should be considered in patients with clinical signs of motor neuron disease.